There Is No Water in the Desert – Implementation of Health Policy Programmes by Local Self Government Units At the Poviat Level in Poland - Kautsch, Marcin; Zientek, Kamila; Szulc, Katarzyna; Piętak, Edyta (Acta Universitatis Lodziensis. Folia Oeconomica, 2023)
Poviat level local government units are obliged to create and implement health policy programmes, which results from the tasks assigned to them in health care. The article verifies to what extent poviats/cities with poviat status fulfill these tasks by implementing health policy programmes, and whether there is a relationship between the implementation of such programmes and the prosperity of the poviat, indicators describing the health of the population and the poviat’s own healthcare hospitals. As a result of the study, it was found that in units that implement health programmes (diseases of affluence, cancer), there are lower death rates. At the same time, only 38% of poviats and 70% of cities with poviat status actually implemented such programmes. The main reasons for such a low percentage of counties forming the above‑mentioned programmes should be considered insufficient structural (law) and institutional (units that can help in the creation of such programmes) support as well as problems with the staff and lack of know‑how of local government units. The development of a central register of programmes, better legislative solutions, modification or development of other models of health policy (focusing on prevention and health promotion) and educational support for local governments could contribute to the improvement of the situation.